2019
DOI: 10.33961/jecst.2018.9.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous Biomass Waste-Derived Activated Carbons for Supercapacitors

Abstract: In the study, herbaceous biomass waste including giant miscanthus, corn stalk, and wheat stalk were used to prepare commercially valuable activated carbons by KOH activation. The waste biomass predominantly consists of cellulose/hemicellulose and lignin, in which decomposition after carbonization and activation contributed to commercially valuable specific surface areas (>2000 m 2 /g) and specific capacitances (>120 F/g) that exceeded those of commercial activated carbon. The significant electrochemical perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…38,40 The residual percentage weights for untreated HW-and MG-biomass samples were 17.2 and 16.4%, respectively, which may indicate their similar lignocellulosic composition contributing to the decomposition. 35 After pretreating the starting biomass samples via slow oxidative torrefaction at 220−300 °C, significant changes in thermal behavior were observed. There was a significant shift in the starting decomposition temperature and also an increase in the residual weights, particularly for samples torrefied at T ≥ 250 °C.…”
Section: Resultsmentioning
confidence: 99%
“…38,40 The residual percentage weights for untreated HW-and MG-biomass samples were 17.2 and 16.4%, respectively, which may indicate their similar lignocellulosic composition contributing to the decomposition. 35 After pretreating the starting biomass samples via slow oxidative torrefaction at 220−300 °C, significant changes in thermal behavior were observed. There was a significant shift in the starting decomposition temperature and also an increase in the residual weights, particularly for samples torrefied at T ≥ 250 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Electrode mass was not mentioned in that paper, although it may have had an impact on the performance of the supercapacitor [24]. Generally, higher electrode mass reduced the specific capacitance [10,11], while slower cycling rates increased the capacitance [25]. Based on the lower usable voltage window, aqueous electrolytes revealed generally lower specific energy than organic electrolytes.…”
Section: Comparison With Other Biobased Supercapacitor Electrodesmentioning
confidence: 95%
“…As a source of the activated carbons, biomass precursors are often used. Examples include specialties (e.g., nanocellulose) and mass products (e.g., paper, textile fibers), as well as waste materials from biorefineries or agriculture [10][11][12]. A comprehensive review covering the literature on the use of polysaccharides as source for these materials showed that there is still large potential for valorizing waste materials into high-performance electrode materials [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been done on the synthesis of carbon materials for electric storage application from different types of biomass waste with different synthesis methods [20,21]. These studies focused on individual biomass waste as a precursor, while studying the effect of different synthesis parameters, such as the types of doping agent, carbonization temperature, and carbonization method.…”
Section: Introductionmentioning
confidence: 99%